The Question of Thermoelectric Devices (TEDs) In/Efficiency—A Practical Investigation Considering Thermoelectric Heaters (TEHs) - Nganyang Paul Bayendang; Mohamed Tariq Kahn; Vipin Balyan (Engineering Reports)
ABSTRACT Thermoelectricity is a promising technology; however, though clean and versatile, its efficiency has been questionable and consequently limiting its extensive utilization. Many published research on thermoelectricity have been on power generation and cooling applications, with few publications on heating, especially practically. Thus, this article practically focuses on thermoelectric devices (TEDs) when used as thermoelectric heaters (TEHs). Sixteen identical TEDs (TEC‐12706) were operated as TEHs under similar test modalities and powered in succession with 12, 10, 8, 6, and 4 V, to practically examine TEHs energy dynamics and in/efficiency. It was found that all the TEHs used in the research performed relatively inconsistent with each other with the worst‐performed TEH (TEH0) having a mean hot‐side temperature of 30.276°C with a mean power consumption of 13.826 W; whereas the best‐performed TEH (TEH3) had a mean hot‐side temperature of 40.4°C with a mean power consumption of 20.822 W. Furthermore, all the TEHs hot‐side temperature increased proportionately with the input voltage; though at the specified voltages, the TEHs hot‐side temperature increased while its input power decreased over time. The concepts of TEH hot‐side mean temperature and TEH mean input power were also introduced.